STUDIES ON GENERALISED UNSTABLE FUNCTIONS IN TOPOLOGICAL SPACES - Vijilius Helena Raj; Srinivasa, G. (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper we bring in a new class of functions called g*Λ irresolute function and contra g*Λ irresolute function, where g*Λ irresolute function is a weaker form of g*Λ continuous function and contra g*Λ irresolute function is a weaker form of contra g*Λ continuous function.